Comparison of proteins, lethality and immunogenic compounds of Androctonus crassicauda (Olivier, 1807) (Scorpiones: Buthidae) venom obtained by different methods - Ozkan,O. (2007)
Scorpions are venomous arthropods of the class Arachnida and are considered relatives of spiders, ticks and mites. There are approximately 1,500 species of scorpions worldwide, which are characterized by an elongated body and a segmented tail that ends in a venomous stinger. No specific treatment is available for scorpion envenomation, except for the use of antivenom. The current study aimed at comparing protein content and lethality of Androctonus crassicauda venom extracted by two different methods (electric stimulation and maceration of telsons). The LD50 calculated by probit analysis was 1.1mg/kg for venom obtained by electric stimulation and 39.19mg/kg for venom obtained by maceration of telsons. In the electrophoretic analysis, protein bands of the venom sample obtained by electric stimulation were between 12 and 53kDa (total: five bands), and those of venom extracted by maceration appeared as multiple protein bands, relative to the other venom sample. Low-molecular-weight proteins, revealed by western blotting, played an important immunogenic role in the production of antivenom. Lethality and protein levels varied according to the extraction method; venom obtained by the maceration technique showed lower toxicity than that obtained by electric stimulation.